Dicyclohexyl phthalate blocks Leydig cell regeneration in adult rat testis. (1st January 2019) - Lv, Yao; Fang, Yinghui; Chen, Panpan; Duan, Yue; Huang, Tongliang; Ma, Leikai; Xie, Lubin; Chen, Xianwu; Chen, Xiaofang; Gao, Jimin; Ge, Ren-Shan
Abstract: Dicyclohexyl phthalate (DCHP) is a phthalate plasticizer with a ring structure in the alcohol moiety. The objective to the current study was to determine the effects of DCHP on Leydig cell regeneration in the adult rat-testis. Adult male Sprague Dawley rats received intraperitoneally an injection of ethane dimethane sulfone (EDS) to eliminate all Leydig cells in the testis and then were divided into 4 groups of 0 (control), 10, 100, and 1000 mg/kg/day DCHP. Rats were gavaged either vehicle (corn oil, control) or DCHP from post-EDS day 7 to day 21 and 28. On post-EDS day 21 and day 28, rats were euthanized and serum testosterone, luteinizing hormone (LH), follicle-stimulating hormone (FSH) levels were measured, and Leydig cell number, cell size, gene, and protein expression were evaluated. During the course of exposure, DCHP did not cause the general toxicity to rats. On post-EDS day 21, DCHP significantly increased serum testosterone level at 10 and 100 mg/kg and increased Leydig cell number at 10 mg/kg via stimulating their mitosis. On post-EDS day 28, DCHP lowered serum testosterone levels and Leydig cell number at 1000 mg/kg. DCHP dose-dependently down-regulated the expression of many Leydig cell genes ( Lhcgr, Scarb1, Star, Cy p11 a1, Hsd3b1, Cyp17a1, Hsd17b3, Hsd11b1, and Insl3 ) and their proteins, especially at 1000 mg/kg. DCHP also lowered the pAKT1/AKT1 and pERK1/2/ERK1/2 ratios. In conclusion, DCHP at low doses (10 and 100 mg/kg) increased Leydig cell number during the initial regeneration and inhibited Leydig cell regeneration during the course of its exposure.